The Impact of Osteopontin Gene Variations on Multiple Sclerosis Development and Progression - Cristoforo Comi; Giuseppe Cappellano; Annalisa Chiocchetti; Elisabetta Orilieri; Sara Buttini; Laura Ghezzi; Daniela Galimberti; Franca Guerini; Nadia Barizzone; Franco Perla; Maurizio Leone; Sandra D’Alfonso; et al. (Clinical and Developmental Immunology)
Osteopontin is a proinflammatory molecule, modulating TH1 and TH17 responses. Several reports suggest its involvement in multiple sclerosis (MS) pathogenesis. We previously reported that OPN gene variations at the 3′ end are a predisposing factor for MS development and evolution. In this paper, we extended our analysis to a gene variation at the 5′ end on the -156G>GG single nucleotide polymorphism (SNP) and replicated our previous findings at the 3′ end on the +1239A>C SNP. We found that only +1239A>C SNP displayed a statistically significant association with MS development, but both +1239A>C and -156G>GG had an influence on MS progression, since patients homozygous for both +1239A and −156GG alleles displayed slower progression of disability and slower switch to secondary progression than those carrying +1239C and/or −156G and those homozygous for +1239A only. Moreover, patients homozygous for +1239A also displayed a significantly lower relapse rate than those carrying +1239C, which is in line with the established role of OPN in MS relapses.